2011
DOI: 10.1002/bjs.7296
|View full text |Cite
|
Sign up to set email alerts
|

Impact of symptom–reflux association analysis on long-term outcome after Nissen fundoplication

Abstract: The subjective and objective outcomes of fundoplication in patients with pathological acid exposure are comparable among those with a positive and negative SAP. Patients with pathological acid exposure and a negative SAP can also benefit from antireflux surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“…However, conflicting data have been reported. Broeders et al have reported similar outcome after fundoplication among patients with a positive and negative SAP 26. In a study assessing the performance of these indices compared with the omeprazole test, SI was shown to be unrelated to the results of the test, whereas SAP had a positive predictive value of 79% and a specificity of 73%; SI and SAP were therefore considered by the authors themselves to be ‘suboptimal’ predictors of response to high-dose omeprazole 13.…”
Section: Discussionmentioning
confidence: 97%
“…However, conflicting data have been reported. Broeders et al have reported similar outcome after fundoplication among patients with a positive and negative SAP 26. In a study assessing the performance of these indices compared with the omeprazole test, SI was shown to be unrelated to the results of the test, whereas SAP had a positive predictive value of 79% and a specificity of 73%; SI and SAP were therefore considered by the authors themselves to be ‘suboptimal’ predictors of response to high-dose omeprazole 13.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding studies ‘off’ therapy, abnormal oesophageal exposure time has been demonstrated to be a predictor of favourable postoperative outcome,130 133 irrespective of the symptom association analysis. Indeed, a recent study reported similar 5-year postoperative outcomes in patients with positive and negative SI/SAP, but with abnormal oesophageal acid exposure, preoperatively 134. Good postoperative outcomes have also been reported when oesophageal acid exposure is within the normal values in patients with a positive symptom association analysis 135 136.…”
Section: Therapeutic Optionsmentioning
confidence: 89%
“…In the last two decades, laparoscopic anti-reflux surgery has been shown to improve the QoL in patients with GERD (Bloomston et al, 2003;Broeders et al, 2010aBroeders et al, & 2011Dallemagne et al, 2006;Draisma et al, 2006aDraisma et al, & 2006bFein et al, 2008;Fernando et al, 2002Fernando et al, & 2003Gee et al, 2008;Gilliesa et al, 2008;Kamolz et al, 2003Kamolz et al, & 2005Morino et al, 2006;Papasevas et al, 2003;Pessaux et al, 2005;Ravi et al, 2005;Rosenthal et al, 2006). In addition to general QoL assessments, several authors also used QoL measurements to compare the effectiveness of different anti-reflux procedures.…”
Section: Symptomsmentioning
confidence: 99%
“…However, lower response rates to PPI treatment and higher relapse rates have also been reported for patients with NERD. In a study, the authors compared subjective and objective outcomes of Nissen fundoplication in ERD and NERD patients operated on for PPI refractory disease (Broeders et al, 2011). Heartburn, regurgitation, and dysphagia grades were similar postoperatively at the five year follow-up.…”
Section: Symptomsmentioning
confidence: 99%
See 1 more Smart Citation